In vitro cell culture models to study hepatitis B and D virus infection - Hongbo Guo; Hongbo Guo; Stephan Urban; Stephan Urban; Wenshi Wang; Wenshi Wang (Frontiers in Microbiology, 2023)
Chronic infection with the hepatitis B virus (HBV) and hepatitis D virus (HDV) can cause a major global health burden. Current medication regimens can repress viral replication and help to control disease progression, but a complete cure is hardly achieved due to the difficulties to eradicate viral templates (cccDNA and integrates). To develop novel curative antiviral therapies for HBV/HDV infection, it is vital to precisely understand the details of the molecular biology of both viruses and the virus-host interactions. One important prerequisite for gaining this aim is the availability of suitable in vitro models that support HBV/HDV infection, replicate both viruses via their authentic template and allow to adequately study host cell responses. The discovery of sodium taurocholate cotransporting polypeptide (NTCP) receptor as the most crucial host factor promoted HBV/HDV research to a new era. Recently, the structure of human NTCP was solved, gaining a deeper understanding of HBV recognition as the bona fide receptor. After decades of continuous efforts, new progress has been achieved in the development of cell culture models supporting HBV/HDV study. This review summarizes the cell culture models currently available, discusses the advantages and disadvantages of each model, and highlights their future applications in HBV and HDV research.